Anxiety and depression among patients with migraine: A single-center cross-sectional study in Malaysia - Sathiapriya Padmanathan; Juen Kiem Tan; Chen Fei Ng; Rathika Rajah; Ching Soong Khoo; Wan Nur Nafisah Wan Yahya; Lai Fong Chan; Michelle Maryanne Tan; Rozita Hod; Hui Jan Tan (PLoS ONE, 2025)
Background Migraine is a chronic neurological problem with a psychological comorbidity. However, anxiety and depression among patients with migraine have not been thoroughly investigated in Southeast Asia. Thus, we aimed to elucidate the prevalence of anxiety and depression in patients with migraine, as well as the associated factors. Methods This cross-sectional study was conducted between March 2022 and March 2024 at the National University of Malaysia. The participants’ data were collected prior to completing two questionnaires, including the Patient Health Questionnaire-9 (PHQ-9) and the Generalized Anxiety Disorder-7 (GAD-7), which were used to evaluate depression and anxiety, respectively. Results A total of 246 participants who were diagnosed with migraine were recruited for this study. The mean age of the participants was 46.19 years (SD: ± 14.75). Additionally, 77.6% of the participants were female. Moreover, 27.7% of the participants had anxiety alone, 15.9% had depression alone, and 11.8% had both anxiety and depression. A younger age (p = 0.03), earlier age of migraine onset (r(246) -0.178, p < 0.01), background history of asthma (r(246) 0.161, p < 0.05), lower household income range (r(246) -0.179, p < 0.01), increased pain severity (r(246) 0.211, p < 0.01), frequency of attack (r(246) 0.139, p < 0.05), use of NSAIDs (r(246) 0.134, p < 0.05), use of pizotifen (r(246) 0.169, p < 0.01), use of propranolol (r(246) 0.286, p < 0.01), use of sodium valproate (r(246) 0.146, p < 0.05), use of topiramate (r(246) 0.178, p < 0.01), use of more than one medication (r(246) 0.240, p < 0.01), use of cold therapy (r(246) 0.223, p < 0.01) and use of acupuncture (r(246) 0.260, p < 0.01) were associated with anxiety and depression in migraine patients. Conclusions Anxiety and depression are commonly observed in patients with migraine in Asia. Routine assessments for anxiety and depression should be performed to ensure holistic management of migraine.